Efficacy and Adverse Effects of Atropine for Myopia Control in Children: A Meta-Analysis of Randomised Controlled Trials - ChunWen Chen; JingYan Yao (Journal of Ophthalmology)
Objectives. To explore the rebound effects and safety of atropine on accommodation amplitude in slowing myopia progression. Methods. We conducted a meta-analysis to testify proper dosage of atropine in children with myopia. We searched in PubMed, EMBASE, Ovid, and the Cochrane Library up to March 30, 2021. We selected randomised controlled trials (RCTs) that evaluated the efficacy of atropine for controlling myopia progression in children. We performed the inverse variance random-effects model to pool the data using mean difference (MD) for continuous variables. Statistical heterogeneity was assessed using the I2 test. Additionally, we conducted subgroup analyses and sensitivity analyses. Results. Seventeen RCTs involving 2955 participants were included. Myopia progression was significantly less in the atropine group than that of the control group, with MD = 0.38 D per year (95% confidence interval, 0.20 to 0.56). Less axial elongation was shown with MD = −0.19 mm per year (95% CI, −0.25 to −0.12). There was a statistically difference among various doses (p=0.00001). In addition, 1.0% atropine showed the rebound effect with MD = −0.54 D per year (95% CI, −0.81 to −0.26) and was more effective in the latter six months than in the former one. Less accommodation amplitude was shown in 0.01% atropine. Conclusion. The efficacy of atropine is dose dependent, and 0.01% atropine may be the optimal dose in slowing myopia progression in children with no accommodation dysfunction. A rebound effect is more prominent in high-dose atropine in the former cessation after discontinuation.